A QUEST FOR A BETTER LIFE AND RACIAL DISCRIMINATION IN BAUCHI EMECHETER’S "SECOND CLASS CITIZEN" - Musa Habib Musa; Muhammad Muhktar (AL-MUTSLA, 2022)
Many black Africans migrate to Europe in search of a better life. However, they face different challenges in the process such as racism, rape, and lack of accommodation in Europe. Thus, this study aims at examining how the quest for a better life and racial discrimination is portrayed in Buchi Emecheter’s Second Class Citizen. The study adopts psychoanalysis theory to analyze the data. The findings of the study show that many Africans consider Europe as heaven, as a source of happiness as a place of freedom and enjoyment while Nigeria and Africa at large as hell. As a result, they want to go and have a better life in the West. Also, the findings show the extent to which Black Africans are racially discriminated against there. They are considered inferior, and unimportant by the whites, and nobody wants to even associate with them. The study identifies some implications of the findings and makes some recommendations for further studies.